On the future of complex problem solving: seven questions, many answers? - Schoppek, Wolfgang; Fischer, Andreas; Funke, Joachim; Holt, Daniel (Journal of dynamic decision making, 2019)
While research on complex problem solving (CPS) has reached a stage where certain standards have been achieved, the future development is quite ambiguous. Therefore, we were interested in the views of representative authors about the attainments and the future development of that field. We asked the authors to share their point of view with respect to seven questions about the relevance of (complex) problem solving as a research area, about the contribution of laboratory-based CPS research to solving real life problems, about the roles of knowledge, strategies, and intuition in CPS, and about the existence of expertise in CPS.